Pengaruh Model Pembelajaran Inquiry Berbantuan Video Animasi terhadap Minat Belajar dan Pemahaman Konsep Matematika Siswa - Harni Astuti, Siti; Masjudin; Sanapiah (Media Pendidikan Matematika, 2025)
This study started from the problem of low interest in learning and lack of understanding of mathematical concepts in elementary school students, especially in the material of circles. To overcome this problem, an inquiry-based learning approach was used which was supported by animated video media. By using an inquiry learning approach assisted by animated videos, this study aims to determine its effect on students' interest in learning and understanding of mathematical concepts. The research activities were carried out in class IV SDN 4 Pringgabaya in the 2024/2025 academic year using a quantitative approach and a quasi-experimental design of the nonequivalent control group design type. The research subjects were divided into two groups, each consisting of 26 students, namely the experimental group and the control group. Data were collected through a questionnaire to assess learning interest and a written test to measure understanding of mathematical concepts. Based on the results of the normality test, the data were not normally distributed, so data analysis was carried out using the Mann-Whitney nonparametric test. The results of the analysis showed a significance value of 0.000 for both aspects studied, namely learning interest and conceptual understanding (p <0.05), indicating a significant difference between the two groups. This shows that the use of animated video-assisted inquiry has proven effective in increasing learning interest and understanding of elementary school students' mathematical concepts.